Freedom's Orphans : Contemporary Liberalism and the Fate of American Children - Tubbs, David Lewis, 1964- (Book collections on Project MUSE., 2007)
Has contemporary liberalism's devotion to individual liberty come at the expense of our society's obligations to children? Divorce is now easy to obtain, and access to everything from violent movies to sexually explicit material is zealously protected as freedom of speech. But what of the effects on the young, with their special needs and vulnerabilities? Freedom's Orphans seeks a way out of this predicament.